Leadership, career growth, and motivation significantly boost job satisfaction in Indonesia: Kepemimpinan, pertumbuhan karier, dan motivasi secara signifikan meningkatkan kepuasan kerja di Indonesia - Firdaus, Moch Alfan; Abadiyah, Rifdah; Adji, Kumara (Indonesian Journal of Law and Economics Review, 2024)
This study examines the impact of leadership style, career development, and intrinsic motivation on job satisfaction at BPR ARTHA MANDIRI. Using a quantitative approach with a sample of 63 employees, data were analyzed using SPSS version 29.0. Results indicate that leadership style, career development, and intrinsic motivation all have significant positive effects on job satisfaction. These findings suggest that improving these factors can enhance employee satisfaction, recommending organizations to focus on effective leadership, career growth opportunities, and fostering intrinsic motivation. Highlight: Leadership, career development, and motivation significantly enhance job satisfaction. Study analyzed 63 BPR ARTHA MANDIRI employees using SPSS 29.0. Improving these factors boosts employee satisfaction and organizational success. Keyword: job satisfaction, leadership style, career development, intrinsic motivation, quantitative research